Demands stated by artistic gymnastics coaches at the beginning of their careers - de Oliveira, L.; Ciampolini, V.; Milistetd, M.; Parra Barbosa-Rinaldi, I.; Pizani, J. (Science of Gymnastics Journal, 2023)
High quality performance of sports coaches involves the use of professional, interpersonal and intrapersonal skills (Côté & Gilbert, 2009). The complexity of the work of sports coaches, especially in Artistic Gymnastics (AG), due to the profound technical and physical demands right from the basic categories, can be magnified for coaches with little experience entering the field. Thus, this study aimed to identify the perceptions of coaches at the beginning of their careers regarding the types of skills required for their professional routine. We interviewed five coaches affiliated with the Santa Catarina Gymnastics Federation (Brazil) with less than 10-year experience in AG. During the interviews, indicators, such as professional routine and knowledge required in this context, were addressed. We used Braun and Clarke's (2019) reflexive thematic analysis to analyze the data. The results show that the complexity of coaches' work requires an expanded repertoire of knowledge. In general, coaches realize that relevant professional and interpersonal skills to teach gymnastics are the most required types of knowledge in daily practice. Intrapersonal skills, on the other hand, seem to be less needed, which may contribute to the preservation of an authoritarian culture in sports training. The requirements discussed in this study lead to implications for and reflections on AG coaches` training programs, especially in the structure of the body of knowledge that provides a good basis for dealing with their daily challenges.